A delicate equilibrium: living with Huntington's disease - Wilson, Eleanor (2013)
Background: People with Huntington’s disease (HD) can be affected by motor, cognitive and behavioural symptoms. The length of the illness trajectory can result in patients receiving care at home for extended periods during which the contribution from family caregivers is invaluable. There has been little research into patient or carer perspectives on needs or how these should be met, and how these correspond to professional viewpoints.